Kepuasan Konsumen melalui Harga, Promosi, Kualitas Makanan dan Kualitas Pelayanan. - Ali Murdhani Ngandoh (STIE AMKOP, 2022)
This study aims to examine the effect of price, promotion, food quality and service quality on consumer satisfaction at Burger King Pettarani Makassar. This type of research is explanatory research. The population in this study were all buyers of Burger King Pettarani Makassar. The number of samples using accidental sampling technique is 90 consumers who are buying or enjoying burger king food at Pettarani Makassar. Data was collected by distributing questionnaires to then analyzed through multiple linear regression analysis using SPSS V.25. The results of the study found that price, promotion, food quality and service quality had a positive and significant effect on consumer satisfaction at Burger King Pettarani Makassar. Keywords: Price, Promotion, Food Quality, Service Quality, Consumer Satisfaction